PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN LQ45 PERIODE TAHUN 2020-2023 - Aulia, Putri; Sukiswo, Helmy Wahyu (Pusat P2M Politeknik Negeri Batam, 2024)
Dividend policy is a strategic decision that involves the allocation of a company's net income after tax to be distributed to shareholders. This research aims to determine the influence of liquidity, profitability and leverage on dividend policy on the LQ45 Index for 2020-2023. This research uses the SPSS test and the sampling method is purposive sampling with the results of obtaining 15 companies as samples. The results of this research prove that liquidity has an effect on dividend policy, profitability has an effect on dividend policy, and leverage has no effect on dividend policy. The independent variables, namely liquidity, profitability and leverage, have an influence on dividend policy by 0.268 or 26.81%, while the remaining 73.19% is influenced by other variables not included in the research.